2016
DOI: 10.18632/oncotarget.7712
|View full text |Cite
|
Sign up to set email alerts
|

PARP6 acts as a tumor suppressor via downregulating Survivin expression in colorectal cancer

Abstract: Poly (ADP-ribose) polymerases (PARPs) are enzymes that transfer ADP-ribose groups to target proteins and are involved in a variety of biological processes. PARP6 is a novel member, and our previous findings suggest that PARP6 may act as a tumor suppressor via suppressing cell cycle progression. However, it is still unclear that PARP6 function besides growth suppression in colorectal cancer (CRC). In this study, we examined tumor suppressive roles of PAPR6 in CRC cells both in vitro and in vivo. We found that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 29 publications
0
24
3
Order By: Relevance
“…Notable genes include: ZFP82 , which is epigenetically silenced and suspected to function as a tumor suppressor (Xiao et al, 2014) (Yu et al, 2015) (Fan et al, 2016); PARP6 hypermethylation (Honda et al, 2016) (Qi et al, 2016); DNAJC15, which is hypermethylated in a number of tumor types (Ehrlich et al, 2002; Lindsey et al, 2006), and whose inactivation has been associated with chemotherapeutic drug resistance in breast (Fernandez-Cabezudo et al, 2016) and ovarian cancers (Rein et al, 2011). We also identified genes that were epigenetically silenced at low prevalence through manual examination of the genes known to be important in cancer, including BRCA1 and MGMT (each silenced in one case).…”
Section: Resultsmentioning
confidence: 99%
“…Notable genes include: ZFP82 , which is epigenetically silenced and suspected to function as a tumor suppressor (Xiao et al, 2014) (Yu et al, 2015) (Fan et al, 2016); PARP6 hypermethylation (Honda et al, 2016) (Qi et al, 2016); DNAJC15, which is hypermethylated in a number of tumor types (Ehrlich et al, 2002; Lindsey et al, 2006), and whose inactivation has been associated with chemotherapeutic drug resistance in breast (Fernandez-Cabezudo et al, 2016) and ovarian cancers (Rein et al, 2011). We also identified genes that were epigenetically silenced at low prevalence through manual examination of the genes known to be important in cancer, including BRCA1 and MGMT (each silenced in one case).…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that overexpression of PARP6 suppressed the cell growth of HeLa cells (14). PARP6 was found to be negatively correlated with the Ki-67 proliferation index, and may be a marker for better prognosis in colorectal adenocarcinoma (13,14). A recent study demonstrated that PAPR6 inhibited colony formation, invasion and cell proliferation in human colorectal adenocarcinoma cell line SW480 (13), and indicated an interaction between the overexpression of PARP6 and the downregulation of survivin.…”
Section: Introductionmentioning
confidence: 99%
“…They play important roles in physiological and pathophysiological processes. Recently, it was shown that PARP6 likely encodes tumor suppressors, and an increase in its methylation was associated with a poor prognosis of various cancer, including hepatoblastoma, colorectal adenocarcinoma (9), breast (10), pancreatic (11), breast (12) and colorectal cancer (13). Among the PARPs, PARP1 is the member which has been studied most extensively.…”
Section: Introductionmentioning
confidence: 99%
“…The facts include (i) the tumor suppression functions of the 10 genes have been demonstrated or suggested in previous publications ( Table 2; refs. [19][20][21][22][23][24][25][26][27][28][29][30][31] and (ii) the methylation statuses in a tumor are well determined by the clearly stratified across-tumor methylation profiles. We also note that these genes can be divided into three categories, representing an uncompleted but a typical taxonomy of potential epi-TSGs.…”
Section: Discussionmentioning
confidence: 99%